Atmospheric, radiative, and hydrologic effects of future land use and land cover changes: A global and multimodel climate picture (2017)
Land use and land cover changes (LULCC) modulate land surface energy, heat, moisture, and momentum fluxes. Using simulations performed with and without LULCC for five earth system models, averaged over the 2071–2100 period, we quantify the biophysical effects in response to a future realistic LULCC scenario (Representative Concentration Pathway RCP8.5) on 15 climate variables (i.e., atmospheric, radiative, wind, hydrologic variables, and heat fluxes). We find that climate models are able to simulate some robust and strong climate perturbations in response to LULCC. In tropical regions with substantial LULCC, significantly higher skin temperatures, less precipitation and soil moisture, less evaporation and clouds, more incoming radiation and stronger winds, more anticyclonic conditions and subsidence, are simulated in response to future LULCC. In midlatitude and high latitude, LULCC result in autumn cooling and higher tropospheric pressures, while East Asia is drier, warmer, with higher sensible heat flux and lower evaporation. The tropical wind strengthening and weakening of the hydrological cycle are comparable in magnitude to their future regional changes induced by greenhouse gases under RCP8.5, which make LULCC an indispensable forcing to take into account in future climatic assessments. Finally, our study reveals significant indirect atmospheric processes triggered by LULCC, implying substantial changes in incoming radiation, which dominate climatic responses over the direct effects, particularly in boreal regions.